Measuring the Level of Relational Coordination Among Higher Education Institutes (HEIs) Professionals - ABID AHMAD; DR. ANJUM IHSAN; DR. ANJUM IHSAN (Journal of Business & Tourism, 2021)
Students’ academic success in Higher Education Institute (HEIs) is highly dependent on effective communication and coordination of its human resources. Relational coordination (RC) explain the performance of tasks that are carried out through coordination and communication among several individuals or groups of individuals.Purpose of this research is to measure the degree of Relational Coordination (RC) among professionals (Teachers, program coordinators, administrative staff, departmental heads and top management) as they perform coordinated tasks targeted at students’ academic success and to identify the week links (where RC is lower) in a reputable private sector HEI in Peshawar, Pakistan. The three relational dimensions (“shared goals, shared knowledge, and mutual respect”) and four communication dimensions (“frequent, timely, accurate, and problem solving communication”) for task integration were used to assess relational coordination.Findings suggested that withinfunction relational links are stronger than the between-function relational ties. within functions relational coordination for Head of Departments and Top Management is relatively strong while it is weak for functional groups of Faculty members and Program Coordinators and weakest for functional group of Administrative staff. The weakest relational coordination is between Program Coordinators and Administrative Staff, Head of Departments and Administrative Staff and Faculty members and Administrative Staff. These are the three weakest links, which calls for interventions on part of management of HEIs.